Recurrent severe hyperbilirubinemia due to compound heterozygous UGT1A1 mutations: an early neonatal presentation of Gilbert syndrome - Joshi, Anjali; Joshi, Jeetinder (International Journal of Contemporary Pediatrics, 2026)
Gilbert syndrome, a relatively common but less conspicuous condition, is characterized by intermittent episodes of mild to moderate unconjugated hyperbilirubinemia due to limited activity of the enzyme UGT1A1. It is usually benign and often remains unnoticed due to overlap with physiological jaundice. We report a case of term male neonate who developed four distinct episodes of severe, recurrent unconjugated hyperbilirubinemia within the first month of life, each requiring intensive phototherapy. Extensive evaluation excluded hemolysis, sepsis, endocrine dysfunction, and cholestatic liver disease as cause of jaundice. Given the atypical presentation with recurrent neonatal jaundice and no identifiable underlying cause, genetic testing was performed, which revealed compound heterozygosity for UGT1A1 variants (-3279T>G promoter polymorphism and 211G>A exon 1 mutation), confirming Gilbert syndrome. The infant responded promptly to phototherapy and had normal BERA and MRI brain with age-appropriate developmental milestones. This case highlights an atypically severe and recurrent neonatal presentation of Gilbert syndrome in the absence of known exacerbating factors and emphasizes the importance of genetic testing to distinguish Gilbert syndrome from Crigler-Najjar syndrome, guide management, and avoid unnecessary invasive interventions.